Implementation of Tahfidzul Qur'an Drill Method in Hamalatul Qur'an Islamic Boarding School - Indra, Damario; Nadlif, Ainun (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research examines the application of the tahfidzul Qur'an training method at the Hamalatul Qur'an Islamic Boarding School. Islamic Religious Education is an essential component of the school curriculum, and the quality of teaching can vary depending on various factors, including the school quality category. This research used a qualitative descriptive method and involved Ustad memorizing the Al-Qur'an at the Hamalatul Qur'an Islamic Boarding School. The research aims to evaluate and understand the practice of the drill habituation method and its implementation in Islamic boarding schools. This research also explores the perceptions of Ustad, Islamic boarding school caregivers, and students regarding this habituation training method. This research uses a descriptive qualitative approach. The research subjects were taught how to memorize the Quran at the Hamalatul Qur'an Islamic Boarding School. Data was collected through interviews with Islamic boarding school administrators Ustad and Santri. The data analysis usually involves several stages, including data reduction, data presentation, and conclusion. The results of this research show that all Al-Qur'an memorizing educators in Islamic boarding schools implemented the drill habituation method before the process of memorizing the Al-Qur'an in accordance with the rules of Islamic boarding school caregivers. The teacher applies habituation training methods in the form of binned or bighorn to students with the aim of providing ease of understanding in learning to memorize the Qur'an.